2014
DOI: 10.1099/ijs.0.053769-0
|View full text |Cite
|
Sign up to set email alerts
|

Terriglobus tenax sp. nov., an exopolysaccharide-producing acidobacterium isolated from rhizosphere soil of a medicinal plant

Abstract: An exopolysaccharide-producing bacterium, designated strain DRP 35 T , was isolated from the rhizosphere soil of a medicinal herb, Angelica sinensis, at Geumsan in Korea. Cells were Gramstaining-negative, non-motile, catalase-positive and oxidase-negative short rods. The isolate grew aerobically from 15 to 45 6C (optimum 30 6C), pH 3.5-7.0 (optimum pH 5.0) and in the presence of 0-1.0 % (w/v) NaCl. The phylum Acidobacteria constitutes one of the most abundant (~20 % of the total bacterial community) and broadl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…2). Acidobacteria strains Granulicella paludicola , G. pectinivorans , G. aggregans and G. rosea (Pankratov and Dedysh 2010), Acidicapsa borealis and A. ligni (Kulichevskaya et al 2012) and Terriglobus tenax (Whang et al 2014) were proven to produce extracellular polysaccharide. By genome mining, Ward et al (2009) have suggested Acidobacteria being involved in soil matrix formation, water and nutrition trapping, or bacterial adhesion that lead to soil aggregate formation.…”
Section: Resultsmentioning
confidence: 99%
“…2). Acidobacteria strains Granulicella paludicola , G. pectinivorans , G. aggregans and G. rosea (Pankratov and Dedysh 2010), Acidicapsa borealis and A. ligni (Kulichevskaya et al 2012) and Terriglobus tenax (Whang et al 2014) were proven to produce extracellular polysaccharide. By genome mining, Ward et al (2009) have suggested Acidobacteria being involved in soil matrix formation, water and nutrition trapping, or bacterial adhesion that lead to soil aggregate formation.…”
Section: Resultsmentioning
confidence: 99%
“…In the Proteobacteria phylum, the genera Bradyrhizobium, Paraburkholderia, Mesorhizobium, Methylobacterium, and Rhizobium were already recognized as mutualistic symbionts of siratro (Angus et al, 2013;Ardley et al, 2014;Borges et al, 2016;Lima et al, 2009). (Armanhi et al, 2018;Cao et al, 2015;Castro et al, 2017;Chou et al, 2007;De Meyer et al, 2015;Hoque et al, 2011;Li et al, 2011;Lu et al, 2017;Sun et al, 2017;Thijs et al, 2014;Whang et al, 2014;Xiao et al, 2017). The other genera isolated have been registered in the literature as endophytic bacteria and plant growth promotors (Chen et al, 2001;Costa et al, 2016;Flores-Félix et al, 2014;Guglielmetti et al, 2013;Guimarães et al, 2012;Jaramillo et al, 2013;Mendis et al, 2018;Souza et al, 2015;Wang et al, 2017;Zhang et al, 2016;Zhao et al, 2017).…”
Section: Groups Strainsmentioning
confidence: 99%
“…These reports include genome mining studies11, description of cultured Acidobacteria species1213 and their interactions with plants14. However, EPS was never isolated and characterized in these studies.…”
mentioning
confidence: 99%